2010
DOI: 10.1007/s10533-010-9438-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-15 signals of leaf-litter-soil continuum as a possible indicator of ecosystem nitrogen saturation by forest succession and N loads

Abstract: Understanding forest carbon cycling responses to atmospheric N deposition is critical to evaluating ecosystem N dynamics. The natural abundance of 15 N (d 15 N) has been suggested as an efficient and non-invasive tool to monitor N pools and fluxes. In this study, three successional forests in southern China were treated with four levels of N addition. In each treatment, we measured rates of soil N mineralization, nitrification, N 2 O emission and inorganic N leaching as well as N concentration and d 15 N of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 62 publications
7
31
0
2
Order By: Relevance
“…Table 1 shows the number of plots (replicates) of planted and natural forests. The presence of naturally occurring Masson's pine forest characterizes the early stage of forest succession in the subtropical zone of China (Fang et al 2011;Yan et al 2009;Zeng et al 2013). Given the implementation of the Natural Forest Conservation Program in China, finding planted Masson's pine forests established on cleared natural forests is challenging.…”
Section: Site Description and Plot Selectionmentioning
confidence: 99%
“…Table 1 shows the number of plots (replicates) of planted and natural forests. The presence of naturally occurring Masson's pine forest characterizes the early stage of forest succession in the subtropical zone of China (Fang et al 2011;Yan et al 2009;Zeng et al 2013). Given the implementation of the Natural Forest Conservation Program in China, finding planted Masson's pine forests established on cleared natural forests is challenging.…”
Section: Site Description and Plot Selectionmentioning
confidence: 99%
“…The δ 15 N source in baseflow mainly derived from soil erosion, local fertilizer application, livestock, plant litter, and deposition from industry, vehicle transportation, and agriculture, but ammonium fertilizers were a minor source of NO 3 − ‐N in the Xiangxi River watershed (Hao, Gao, et al, ), which was similar to results from other studies conducted around the Yellow River (Yue, Li, Liu, Zhao, & Ding, ). Our study also showed that the NO 3 − consumption rate that derived from denitrification was higher than the NO 3 − production rate derived from nitrification, which led to changes in δ 15 N enrichment in soil solutions (Cheng, Fang, Yu, Zhu, & Zheng, ; Fang et al, ; Yue, Li, CQi, Lang, & Ding, ). This is because denitrification of the remaining nitrates will take place via N isotopic enrichment (Gooddy et al, ; Li et al, ).…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies suggest soil P availability might be a more important limiting factor of ecosystem primary production and litter microbial activity than soil N availability in all study forests (Hou et al 2012;Liu et al 2012;Zhu et al 2014) except the PF where the opposite might be true (Hou et al 2012). Lower plant materials d 15 N in the pine forest than the other forests were probably due to its significantly lower soil N availability (Table 2; Fang et al 2011a), which was further attributable to the harvest practice that had removed a considerably amount of nutrients from the site (Mo et al 1995). In contrast, high leaf d 15 N in the ravine forests was likely to be related to their high soil P availability as demonstrated by the multiple regression analysis (Online Resource 6).…”
Section: Plant and Soil D 15 N In Relations To Selected Plant And Soimentioning
confidence: 77%
“…Indeed, no significant or even negative relationships between leaf d 15 N and N supply have been reported in some other studies (Clarkson et al 2005;Fang et al 2012Fang et al , 2011bMcKee et al 2002). The inconsistent relationships between leaf d 15 N and N supply in different studies were probably related to the varied site characteristics in different areas, such as soil N and P supplies (Clarkson et al 2005;Fang et al 2011a;McKee et al 2002), the level, composition, and/or the stable isotope signature of regional atmospheric N deposition (Fang et al 2012(Fang et al , 2011bPardo et al 2006). …”
Section: Plant and Soil D 15 N In Relations To Selected Plant And Soimentioning
confidence: 95%